2019
DOI: 10.1371/journal.pone.0213925
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference values for selected haematological parameters in young adult Nigerians

Abstract: Background Haematological reference values are necessary for accurate diagnosis of diseases, clinical decision-making, treatment monitoring and clinical research. Due to unavailability of pan-Nigerian reference values, local results interpretation is based on the use of Western values. Objective This study aims to establish national reference values for some haematological parameters in apparently healthy young adult Nigerians. Methods Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…We observed that the mean Hb concentration and Hct of the participants were 13.0 g/dl and 40% respectively in our study. This corroborates previous research findings among blood donors [21], but lower than reported by Ayemoba et al [15]. Our study recorded a median total white cell count of 4.9/nl among studied subjects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that the mean Hb concentration and Hct of the participants were 13.0 g/dl and 40% respectively in our study. This corroborates previous research findings among blood donors [21], but lower than reported by Ayemoba et al [15]. Our study recorded a median total white cell count of 4.9/nl among studied subjects.…”
Section: Discussionsupporting
confidence: 93%
“…The majority (85.4%) of the subjects were between ages18 and 39 years old. The demographic findings in this study were comparable with reports from previous studies among prospective whole blood donors in Nigeria [9] [14] [15]. The predominance of the younger people in the blood donor pool may be explained by the fact that the youth have a better knowledge about blood donation, through being vast in digital technology.…”
Section: Discussionsupporting
confidence: 88%
“…Korea 2018 [27] Thai 2018 [23] Nigeria 2019 [25] Brazil 2019 [10] Iraq 2020 [13] Iran 2021 [7] Age Canada 2015 [35] Kuwait 2016 [14] Mali 2017 [2] Oman 2018 [3] Kenya 2018 [41] Korea 2018 [27] Thai 2018 [23] Nigeria 2019 [25] Brazil 2019 [10] Iraq 2020 [13] Iran 2021 [7] F menstruation (34). In the current study, the platelet-related findings are consistent with literature (1,27,32,42).…”
Section: [41]mentioning
confidence: 99%
“…Studies have equally reported significantly higher values of reticulocyte counts, RBC counts, HGB, and HCT% in adult males compared to the females [ 1 , 2 , 9 , 17 , 20 22 ]. B12 deficiency and comorbidities were more common in elderly men [ 23 ], while in a population-based study among healthy Ugandan population, RBC counts, HGB, and HCT% were higher in adult males than females [ 2 ].…”
Section: Resultsmentioning
confidence: 99%